1981
DOI: 10.1111/j.1468-2982.1981.tb00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Ergotamine Abuse. Do Patients Benefit from Withdrawal?

Abstract: A follow-up study of 40 patients (migraine 39, cluster headache 1) previously treated for ergotamine abuse was conducted. Their statements regarding ergotamine intake were checked using butalbital (contained in the suppositories abused by 90% of the patients) as a tracer, and later by contact with the family doctor. Eleven patients abused ergotamine again during a median observation time of 21 months. Nineteen patients had more than a 50% reduction in headache days after withdrawal and half of the patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
4

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 11 publications
0
47
0
4
Order By: Relevance
“…Later reports by Andersson [5] and Tfelt-Hansen and Krabbe [6] confirmed this pattern and also reported that recidivism to use of ergotamine with recurrence of severe rebound headache occurred in 33% to 50% of subjects withdrawn from these medications. Subsequent work identified a similar pattern in those using daily butabarbital.…”
Section: Rebound-withdrawal Headache (Medication Overuse Headache)mentioning
confidence: 69%
See 1 more Smart Citation
“…Later reports by Andersson [5] and Tfelt-Hansen and Krabbe [6] confirmed this pattern and also reported that recidivism to use of ergotamine with recurrence of severe rebound headache occurred in 33% to 50% of subjects withdrawn from these medications. Subsequent work identified a similar pattern in those using daily butabarbital.…”
Section: Rebound-withdrawal Headache (Medication Overuse Headache)mentioning
confidence: 69%
“…In the period from 1950 to 1980, the concept of headache related to medication overuse was developed by Peters and Horton [2], Friedman et al [3], and Kudrow [4] in America, and by Andersson [5] and TfeltHansen and Krabbe [6] in Europe. In the 1970s, debates about tension headache with secondary vascular component versus vascular headache with secondary tension component were frequently heard.…”
Section: Background Of the Diseasementioning
confidence: 99%
“…The duration of chronic drug overuse was found by some authors to be a significant parameter [27][28][29]; for example, the type of analgesic abused was relevant in maintaining CDH and drug abuse [29][30][31]. On the other hand, others did not find any significant prognostic factor for long-term outcome in CDH patients [32,33].…”
Section: Discussionmentioning
confidence: 90%
“…With regard to ergotamine withdrawal, Andersson [18] and Tfelt-Hansen and Krabbe [19] noted that there was a 33% to 50% rate of recidivism to ergotamine use in patients withdrawing from ergotamine. Diener and Dahlöf [10] and Katsarava et al [20] have suggested that cautious re-exposure to triptans may not trigger recurrent MOH.…”
Section: Medication-overuse Headachementioning
confidence: 98%